Eksplorasi Teologi Kovenan dan Kepastian Janji Allah dalam 2 Korintus 1:20 pada Dinamika Spiritual Jemaat - Daniel Pesah Purwonugroho (Sekolah Tinggi Teologi Nusantara, 2024)
This paper is crafted with the aim of exploring covenant theology and the certainty of promises in 2 Corinthians 1:20 concerning the spiritual dynamics of the congregation. Covenant theology frames the interaction between God and humanity and is divided into two systems: the covenant of works and the covenant of grace, each with distinct focal points. Jesus Christ plays a significant role in both systems, fulfilling the covenant of works and serving as the mediator between God and humanity within the covenant of grace. Jesus Christ is also the central figure of God's promises, as expressed in 2 Corinthians 1:20. God's promises have a significant impact on the spiritual life of the congregation. In addition to God's promises, covenant theology positively influences the spiritual dimension of the congregation. Through a descriptive qualitative approach, the author explores covenant theology and the certainty of promises in 2 Corinthians 1:20 for the congregation's spiritual dynamics. The author asserts that the exploration of covenant theology and the certainty of promises in 2 Corinthians 1:20 has a significant positive impact on the spiritual dynamics of the congregation. AbstrakTulisan ini dirangkai dengan tujuan untuk mengeksplorasi teologi kovenan dan kepastian janji dalam 2 Korintus 1:20 pada dinamika spiritual jemaat. Teologi kovenan merupakan teologi yang membingkai interaksi Allah dengan manusia. Teologi kovenan terbagi dalam 2 sistem yaitu kovenan kerja dan kovenan anugerah dimana masing-masing kovenan memiliki titik tumpu yang berbeda. Yesus Kristus memiliki peran signifikan di dalam 2 sistem tersebut dimana Yesus Kristus menggenapi kovenan kerja dan menjadi perantara Allah dan manusia di dalam kovenen anugerah. Yesus Kristus juga menjadi pusat janji Allah yang dinyatakan di dalam 2 Korintus 1:20. Janji Allah memilki dampak yang signifikan dalam membangun kehidupan rohani jemaat. Selain janji Allah, teologi kovenan juga memberikan pengaruh positif di dalam sisi spiritual jemaat. Melalui pendekatan kualitatif deskriptif, penulis akan mengeksplorasi teologi kovenan dan kepastian janji dalam 2 Korintus 1:20 bagi dinamika spiritual jemaat. Penulis menegaskan bahwa eksplorasi teologi kovenan dan kepastian janji dalam 2 Korintus 1:20 memberi dampak positif yang signifikan di dalam dinamika spiritual jemaat yaitu jemaat akan mengalami pertumbuhan rohani baik secara individu maupun secara komunal.